Myomectomy during cesarean section or non-caesarean myomectomy in reproductive surgery: this is the dilemma - Andrea Tinelli; Ceana H. Nezhat; Ivana Likić-Ladjević; Mladen Andjić; Dina Tomašević; Dimitrios Papoutsis; Radomir Stefanović; Radmila Sparić (IMR Press, 2021)
Nowadays it is quite common to encounter pregnants over 35 years with uterine fibroids (UFs), requiring cesarean section (CS). Large UFs may cause severe complications during delivery, as bleeding and hemorrhage, during vaginal or cesarean delivery. Frequently, the caesarean myomectomy (CM) is recommended, but generally obstetricians are reluctant to perform CM, since literature data do not agree on its surgical recommendation. CM is jet particularly controversial, due to increased risk of perioperative hemorrhage and cesarean hysterectomy, and UFs are often left in situ during cesarean section (CS). CM investigations are generally directed to myomectomy associated issues, whereas CS complications without CM are largely underreported. The risks of leaving UF for an interval myomectomy is underestimated and large UFs, left in uterus during CS, might cause significant early and late postoperative complications, even necessitating a relaparotomy and/or a subsequent hysterectomy. CM would be mandatory in some instances, whatever the UF diameter, to avoid further damage or complications. UFs management prior to CS should include a full counselling on pro and cons on the possible consequences of surgical decisioning. To illustrate what was discussed above, authors performed a narrative review with an expert opinion, reporting a case of a 31-year-old woman with a large UF who underwent a CS without myomectomy. Nine hours after CS, puerpera was submitted, for a massive postoperative hemorrhage and hemorrhagic shock, to an emergency relaparotomy with total hysterectomy without salpingo-oophorectomy.